The road to Nissan : - Wickens, Peter (Macmillan press, 1987)
The Road to Nissan goes beyond the superficial and describes the worldwide influences on Nissan's initiatives. It explodes many stereotypes about Japanese management but distills those elements which are transferable and shows how this can be achieved. The author also vigorously challenges much recent Western management thinking, offering specific remedies and proposing a totally integrated strategy aimed at achieving mutual trust and commitment with everyone working towards a common goal.